PROSES PRODUKSI STAND GRIPPER MENGGUNAKAN CNC MILLING 3 AXIS TIPE WELLE CV 1060 - Dimas Andika Yudistira; sabilla, Jetma Sabilla; Afiq Khairul Ikhwan (Accurate: Journal of Mechanical Engineering and Science, 2023)
One of the efforts made in the education sector to increase the need for human resources is to implement a system that can create a workforce that is ready to apply their knowledge in the field of work. To apply the knowledge they have gained while attending lectures, students are given the opportunity to go directly to a company which is usually called an industrial internship. While carrying out industrial internships at Solo Technopark, students are placed in the CNC design and machining section. The stand gripper production process goes through several stages, namely designing product images, creating a numerical control program with Autodesk powermill software, and computer numerical control milling (CNC milling) machining processes. The problem that occurs during the stand gripper production process is that there is very little material gripping due to the size of the initial material which has very little difference with the size of the finished workpiece. The solution to this problem is to ensure strong clamping and the help of parallel blocks so that the material does not move during the execution of the workpiece.